Pricing the priceless : the financial transformation to value the planet, solve the climate crisis, and protect our most precious assets - DiPerna, Paula (Ascent Audio, 2023)
In Pricing the Priceless, renowned environmental strategist, speaker, world traveler, and author Paula DiPerna brings a unique voice and optic to demystify and unveil today's most fascinating financial disruption-pricing the priceless to flip conventional ideas of how we value natural assets and why. She asks the provocative question long ignored: Why do we value the indispensable atmosphere at zero, but dispensable production in the trillions? She digs into alternatives, with real-life examples from around the globe of fascinating and pioneering financial innovations. With power, clarity, and real-world experience, the author also examines: fascinating new financial inventions and experiments-insurance, bonds, markets, investment funds-all aimed at pricing what is precious and vital to human well-being; how the great current intergenerational shift in wealth and attitudes is redefining investment trends and the idea of what constitutes wealth and return; how climate change and other urgent environmental problems now require entirely new financial thinking to trigger solutions; how once-radical ideas about measuring economic progress are now reimagining the very purpose of capitalism; and why finance needs critical reinvention to remain credible in the face of increasing public skepticism of business-as-usual economic practice.